Proton drip line evaluation by complementing the Finite Range Droplet Model with neural networks - Athanasopoulos, S.; Mavrommatis, E.; Gernoth, K. A.; Clark, J. W. (HNPS Advances in Nuclear Physics, 2020)
We evaluate the location of the proton drip line in the regions 31≤Z≤49 and 73≤Z≤91 based on the one- and two-proton separation energies predicted by our latest Hybrid Mass Model. The latter is constructed by complementing the mass-excess values ΔM predicted by the Finite Range Droplet Model (FRDM) of Moeller et al. with a neural network model trained to predict the differences ΔMexp − ΔMFRDM between these values and the experimental mass-excess values published in the 2003 Atomic Mass Evaluation AME03.